Kajian Budaya Organisasi Bina Nusantara University Menuju â€œA World Class Universityâ€ - Luthfia, Amia; Wasita, Agus; Syaukat, Rosidah (Bina Nusantara University, 2013)
University is an important institution that would form the nation culture and responsible for the culture transmission. The assessment of a good organizational culture is an important part in the study of organizational culture. The research objective is to analyze organizational culture of Bina Nusantara University comprehensively, the strengths and weaknesses of its effort to become ?The World Class University